LINGUISTIC ANALYSIS OF LEGAL TERMINOLOGYIN ENGLISH AND UZBEK - Xasanbayeva Saodat A'zamjon qizi, (TADQIQOTLAR, 2025)
Abstract:  Legal  terminology  represents  a  specialized  and  highly conventionalized layer of vocabulary that ensures accuracy, consistency, and clarity in legal communication. This article provides a linguistic analysis of legal terminology in the English and Uzbek languages, with particular attention to its structural, semantic, and functional features. The study aims to identify both common and language-specific characteristics of legal terms that arise from differences in linguistic systems, legal traditions, and sociocultural contexts. The research employs descriptive and contrastive methods to examine morphological patterns, word-formation processes, and semantic properties  of  legal  terms  used  in  statutory  texts,  legal  documents,  and  judicial discourse.  Special  emphasis  is  placed  on  terminological  precision,  polysemy, synonymy, and the issue of partial or non-equivalence between English and Uzbek legal terms. The analysis also addresses the pragmatic function of legal terminology, demonstrating how terms operate within institutional discourse to regulate meaning and  minimize  ambiguity.  The  findings  reveal  that  while  English  and  Uzbek  legal terminologies share universal features such as formalization and stability, they differ significantly  in  their  lexical  composition,  borrowing  strategies,  and  syntactic realization.  These  differences  often  create  challenges  in  legal  interpretation  and translation.